On the Optimal Compensation of a Socialist Manager - Domar, Evsey D. (Quarterly Journal of Economics, 1974)
I. The problem, 1. — II. The bonus as a function of profit and sales, 4. — III. The iterative process, 9. — IV. A practical look, 12. — Mathematical note, 15.